Locations, Circumstances, and Outcomes of Falls in Patients with Glaucoma - Sotimehin, Ayodeji E. (Am J Ophthalmol, 2018)
PURPOSE: To characterize the locations, circumstances, and outcomes of falls in patients with varying degrees of glaucoma. DESIGN: Prospective cohort study METHODS: Patients with suspected or diagnosed glaucoma completed monthly calendars reporting falls. After each fall, a 30-item questionnaire was administered to determine fall location, circumstances, and injury. Mean deviation on visual field (VF) testing was used to categorize glaucoma severity. MAIN OUTCOME MEASURES: Fall locations, circumstances, and outcomes. RESULTS: One-hundred forty-two patients experienced 330 falls. Falls were most likely to occur in/around the home (71%), and this likelihood did not vary significantly with severity of VF damage (p >0.2). The most commonly cited fall circumstances were tripping, (43.6%), slipping (31.3%), uneven flooring (23.5%), and poor vision (15.9%). The circumstances related to falls did not vary by severity of VF damage (p>0.2) except for poor vision, which was more frequently cited in individuals with more advanced VF damage (p=0.001). Forty-three percent of falls resulted in some injury; and the likelihood of injury did not vary by severity of VF loss (p=0.60) or any other factor except floor type and number of comorbidities (p< 0.05 for all). Falls in persons with more severe glaucoma were more likely to result in a fracture (9.4%) or an ER visit (18.8%), though these associations did not persist in multivariable models (p>0.5 for all). CONCLUSIONS: Glaucoma patients fall mostly in/around the home and demonstrate similar fall circumstances across the spectrum of disease severity, suggesting that current fall-prevention-interventions, particularly those emphasizing home modification, may be an adequate starting point to prevent falls in this high-risk-group.